Improved Understanding Of Greenwashing And Green Consumer with Rasch Model Analysis - Putri, Yulia Hamdaini; Rosa, Aslamia; Mavilinda, Hera Febria (Jurnal Bisnis dan Manajemen, 2021)
As extensive information comes so fast, increasing consumer awareness of greening the environment increases. Environmental damage caused by human waste, natural disasters, and non-renewable natural resources, and damage to natural ecosystems makes consumers careful in purchasing decisions. This study aims to know indicators in the greenwashing and green consumers which one the least liked or preferred based on the gender of generation Z. Method of analysis is using the Rasch model. A sample of 340 respondents generation Z. The result is green consumers (consumers throw garbage in their place, water-saving consumers, consumers like cleanliness). Consumers are willing to pay more to get the product labelled eco-product/ go green. This study is limited to explaining the response of generation Z regarding the items contained in the greenwashing and green consumer variables.